A Narrative Review on Ethnomedicinal Relevance and Species Diversity of Opuntia Genus in India - S Raj, Asha; Acharya, Rabinarayan; R Patel, Bhupesh (Pharmacognosy Reviews)
Opuntia genus belonging to Cactaceae family has been considered as a weed in various parts of world. It grows extensively all over India particularly in dry areas. Folklore practitioners across India make use of various parts of this plant in innumerable disease conditions. The present review aims to collect all available ethnomedicinal information on various species of Opuntia in India. Review has been done on the ethnomedicinal uses of Opuntia genus reported in India has been collected from books on ethnobotany and ethnomedicinal research articles which have been compiled from library sources and web-based search engines like Google Scholar, PubMed, ScienceDirect, J-Gate etc from Feb.2021-Nov. 2021. Each particular species of Opuntia reported along with vernacular name, place of reporting along with the therapeutic indication, with specific method of administration and other uses if any were also noted. From 122 articles reviewed, members of Opuntia genus are found to be available in 16 states across India, with well-established folklore claims. It has reported to be used in 85 different clinical conditions with some potential leads for reverse pharmacological studies. It is also noted that all parts of certain species like Opuntia dillenii Haw. are used, whereas Opuntia vulgaris Mill. are less used when compared. Conclusion: Opuntia genus has been claimed for multifaceted ethnomedicinal uses. These ethnomedicinal claims serves as “a lead” for many pharmacological activities which has to be substantiated with suitable in vivo and clinical evaluations.
Keywords: Ethnomedicine; Opuntia genus; India; O. dilleni; O. elatior